Homogenization-induced age-hardening behavior and room temperature mechanical properties of Mg-4Zn-0.5Ca-0.16Mn (wt%) alloy. (15th February 2019) - Duley, Partha; Sanyal, Souriddha; Bandyopadhyay, T.K.; Mandal, Sumantra
Abstract: The cast Mg-4Zn-0.5Ca-0.16Mn (wt%) alloy, prepared through conventional melting-casting route, exhibits appreciable strength (UTS~180 MPa, YS~175 MPa) with limited elongation (<1%). As the cast specimens are subjected to homogenization treatments for 6–72 h at 633 K, the yield strength decreases by an acceptable margin (97–117 MPa) accompanied by a noteworthy increase in ductility (3.2–8.5%). The improvement in ductility is primarily due to the dissolution of the coarse networks of the eutectic Ca2 Mg6 Zn3 phase formed during casting. Interestingly, the work hardening response of the alloy also improves with homogenization. The evolution of grain size heterogeneity, the presence of Mn particles and the evolution of β 1 ′ precipitates have been identified as the major contributing factors behind this. The β 1 ′ precipitates predominantly form at the interface of the Mn particles/Mg matrix and evolve by changing the aspect ratio during homogenization treatment. This evolution of β 1 ′ precipitates is accountable for the age-hardening kind of response of the alloy where the three conditions, namely under-aging, peak-aging, and over-aging, can be distinguished clearly in terms of hardness and strength. The homogenization duration of 24 h has been identified to generate a better combination of strength, ductility and work hardening response in the studied alloy. Graphical abstract: Highlights: Dissolution of eutectic Ca2Mg6Zn3 phase during homogenization enhances ductility. Mg4Zn7 ( β 1 ′) phases form at the Mg-Mn interfaces during homogenization. Evolution of β 1 ′ phase during homogenization exerts age-hardening type response. Mn and β 1 ′ phases enhance yield strength in the homogenized specimens. Grain size heterogeneity and precipitation (Mn, β 1 ′) improves work-hardening.